Comprehensive Assessment of COVID-19 Vaccine Efficacy, Immunogenicity, and Safety: A Systematic Review - Hadi Shnar Jabr Lsloom; Omar Mohammed Bidah Alnawfal; Samirah Hamadi Mohammed Maashi; Fatemah Abdullah Abdulaziz Alhubaishi; Reham Ali Mohammed Aljurayad; Alshahrani, Nahar Munyif M; Saeed Alqahtani, Nawaf Mansour (International Journal of Medical Toxicology and Legal Medicine, 2024)
Following the World Health Organization's (WHO) announcement of the Coronavirus Disease 2019 (COVID-19) pandemic in January 2020, the want for ongoing monitoring has been emphasized because of sudden traits associated with Coronavirus Disease 2019 (COVID-19) vaccination. This research explores a systematic synthesis of studies to evaluate the lasting effectiveness, immune response, and protection of Coronavirus Disease 2019 (COVID-19) vaccines. Additionally, the evaluation consists of the crucial consideration of tackling new variants. Methodology: This research constitutes an umbrella review focusing on the viability and efficacy of Coronavirus Disease 2019 (COVID-19) vaccines.A thorough investigation was conducted across PubMed, Web of Science, and Scopus databases, utilizing keywords associated with Coronavirus Disease 2019 (COVID-19) vaccination. Inclusion criteria centered on peer-reviewed systematic reviews and meta-analyses in English, explicitly emphasizing feasibility and efficacy. Exclusion parameters targeted non-systematic reviews solely concerning vaccine safety and eliminated duplicates. Data synthesis encompassed narrative and potentially quantitative synthesis through metaanalysis, adhering to PRISMA guidelines. Results: The study encompassed 23 systematic reviews. Findings suggested that Coronavirus Disease 2019 (COVID-19) vaccines generally exhibit both safety and efficacy across a spectrum of medical conditions. The overall bias risk for the included studies was deemed low. Conclusions: The examine's effects indicated that mRNA vaccines present a better incidence of unfavourable events however demonstrate superior efficacy. Conversely, inactivated and better protection profiles signify protein subunit vaccines however show off reduced effectiveness. Furthermore, the vaccine became deemed secure for individuals with particular conditions which include inflammatory bowel disorder, stable organ transplant recipients, children, pregnant individuals, and those with hematologic disorders. Ultimately, man or woman attractiveness of the Coronavirus Disease 2019 (COVID-19) vaccine is motivated by using many elements, consisting of geographical, socioeconomic, and pandemic-related issues.